Targeting a "hot loop" in the oncogenic Skp2-Cks1 protein-protein interaction with cyclic peptide inhibitors. - Keenan, Caitlin M. (Tufts University. Tisch Library., 2015)
This project involves the development of conformationally constrained mimetic peptides, informed by the Loop Finder program developed by the Kritzer Lab, to block the interaction between two subunits of a ubiquitin ligase. This protein-protein interaction is involved in regulating progression from G1 to S phase of the cell cycle and is associated with many types of cancer. Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.